Soft giant magnetoimpedance electronics enable contact-free human–machine interactions - Yizhang Wu; Sicheng Xing; Dingyi Yang; Yihan Liu; Chi Ding; Zifeng Li; Qizhang Jiao; Anran Zhang; Ziheng Guo; Siyuan Liu; Wei Luo; Gongkai Yuan; et al. (Proceedings of the National Academy of Sciences, 2026)
Magnetic sensing enables contact-free, three-dimensional human–machine interactions (HMI) with high selectivity and resilience to environmental noise. However, conventional magnetic films, mostly obtained via vacuum deposition, remain constrained by rigidity, instantaneous response, and single-mode. Here, we report a giant magnetoimpedance ionogel (GelGMI) in which electrostatically self-assembled ferromagnetic (FM) domains are uniformly dispersed in a soft ionogel matrix. Under a magnetic field, domain moments realign to reconfigure ionic pathways, yielding pronounced magnetoimpedance while maintaining performance at >1,000% strain and across orientations. The hysteretic relaxation of domain magnetization imparts retrospective neuron-like temporal summation, realizing sequence- and context-aware interaction. In addition, the self-healable matrix supports a complementary tactile mode whose impedance contrasts with contact-free magnetic proximity, enabling expandable and bimodal recognition. GelGMI delivers a record-high sensitivity while unifying stretchable, neuromorphic, and healable capabilities for contact-free HMI systems.